2013
DOI: 10.1007/s00784-013-1161-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of four different irrigation systems in the removal of a root canal sealer

Abstract: Incomplete removal of root canal sealer during re-treatment may cause treatment failure. Passive Ultrasonic irrigation seems to be the most effective system to remove sealer from a root canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 39 publications
4
45
1
6
Order By: Relevance
“…However, according to the results, this ability of PUI did not allow a greater amount of gutta-percha and sealer to be removed, as compared with the control group. This result differs from that found by Grischke et al 16 . These authors noted that the cleansing effect of PUI with NaOCl was superior to all the other irrigation techniques in removing root canal sealer.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, according to the results, this ability of PUI did not allow a greater amount of gutta-percha and sealer to be removed, as compared with the control group. This result differs from that found by Grischke et al 16 . These authors noted that the cleansing effect of PUI with NaOCl was superior to all the other irrigation techniques in removing root canal sealer.…”
Section: Discussioncontrasting
confidence: 99%
“…PUI has the potential to remove dentinal debris, organic tissue, and calcium hydroxide from inaccessible root canal areas [13][14][15] . Recently, Grischke et al 16 evaluated the use of ultrasound in the removal of a root canal sealer both from the surface and from simulated irregularities of root canals. The authors found that the ultrasonic irrigation protocol was superior to the other techniques investigated in the removal of sealer from the root canal surface during endodontic retreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have evaluated different retreatment systems without solvent to prevent the interference of a thin layer of gutta-percha which forms and adheres to the root canal walls (16,20,31). Grischke et al (10) found that PUI can remove AH Plus root canal sealer from the root canal surface of straight canals with simulated irregularities better than syringe irrigation. The presence of these irregularities may increase the influence of PUI on sealer removal.…”
Section: Discussionmentioning
confidence: 99%
“…manual files, rotary and reciprocating instruments and sonic or ultrasonic irrigation (6)(7)(8)(9)(10)(11). However, all retreatment techniques have been found to leave some residual gutta-percha and sealer on canal walls after re-instrumentation (12).…”
Section: Introductionmentioning
confidence: 99%
“…However, within the consideration of the currently available re-treatment studies, the results have shown the remnant filling materials to be remained through the canal walls even if solvents or rotary/hand instruments have been applied. [16][17][18][19] Therefore, the re-treatment protocol has to be supported with some additional irrigation systems, medicaments and/or irrigants to obtain total remove of root filling material and to reach all the points in root canals regarding uninstrumented areas which depends on the complex anatomy.…”
Section: Discussionmentioning
confidence: 99%